Polymorphisms of Homologous Recombination RAD51, RAD51B, XRCC2, and XRCC3 Genes and the Risk of Prostate Cancer. (3rd August 2015) - Nowacka-Zawisza, Maria; Wiśnik, Ewelina; Wasilewski, Andrzej; Skowrońska, Milena; Forma, Ewa; Bryś, Magdalena; Różański, Waldemar; Krajewska, Wanda M.
Abstract : Genetic polymorphisms in DNA repair genes may induce individual variations in DNA repair capacity, which may in turn contribute to the risk of cancer developing. Homologous recombination repair (HRR) plays a critical role in maintaining chromosomal integrity and protecting against carcinogenic factors. The aim of the present study was to evaluate the relationship between prostate cancer risk and the presence of single nucleotide polymorphisms (SNPs) in the genes involved in HRR, that is, RAD51 (rs1801320 and rs1801321), RAD51B (rs10483813 and rs3784099), XRCC2 (rs3218536), and XRCC3 (rs861539). Polymorphisms were analyzed by PCR-RFLP and Real-Time PCR in 101 patients with prostate adenocarcinoma and 216 age- and sex-matched controls. A significant relationship was detected between the RAD51 gene rs1801320 polymorphism and increased prostate cancer risk. Our results indicate that the RAD51 gene rs1801320 polymorphism may contribute to prostate cancer susceptibility in Poland.